THE DEVELOPMENT OF INTERNET SLANG AND ITS IMPACT ON YOUTH SPEECH - Pulatova Ugilkhan Sobirjon kizi (International Journal of Literature and Language Studies, 2026)
The rapid growth of social media and digital communication has significantly influenced the language used by young people. Internet slang includes abbreviations, acronyms, shortened words, respellings, emojis, and newly created expressions commonly used on social networking platforms, messaging applications, online games, and discussion forums. This study examines the development of English internet slang and its influence on the spoken and written communication of young people. The research employs a qualitative literature-review method and synthesizes findings from studies on computer-mediated communication, digital discourse, youth language, and sociolinguistics. The results indicate that internet slang develops through abbreviation, clipping, semantic change, word formation, and the transformation of online expressions into spoken language. Internet slang helps young people communicate quickly, express emotions, construct social identities, and strengthen group solidarity. However, its excessive or contextually inappropriate use may negatively affect formal writing, communication between generations, and the ability to distinguish between formal and informal registers. The study concludes that internet slang should not be regarded simply as linguistic deterioration. Instead, it represents language creativity and adaptation to digital environments. Language educators should therefore teach students how to use internet slang appropriately while maintaining competence in standard English.